A thematic analysis of in-hospital end-of-life care experiences of surviving family members. Issue 6 (3rd July 2021) - Johnson, Shannon; Kelemen, Anne; Grimes, Coleia; Stein, Susannah; Groninger, Hunter
Abstract: While end-of-life care (EoLC) priorities for patients dying in the hospital are well-documented, few data characterize needs and experiences of their family members. We conducted thematic analysis of audio recorded interviews of 18 bereaved family members to elucidate these experiences. Participants' memories were organized into two parent themes: those related to satisfaction with the care received and effective communication; those identifying shortcomings in patient care, hospital-family communication, hospital environment, and care burden on the part of family members. These findings provide insight to enhance services to patients and their families at end-of-life and improve postmortem and bereavement services.